Study on landscape quality assessment of urban forest parks: Take Nanjing Zijinshan National forest Park as an example. (January 2021) - Han, Xiuyan; Sun, Tao; Cao, Tianyi
Graphical abstract: Highlights: Environmental pollution affected the landscape quality of Urban Forest Park. LQ assessment indicator system of urban forest park with multi-index was constructed. Landscape quality of urban forest park by niche suitability model was assessed. The change law of LQ in Nanjing Zijinshan National Forest Park was explored. Abstract: In order to explore assessment methods of landscape quality (LQ) of Urban Forest Park, based on the literature review and current situation analysis, this paper selected 26 assessment indicators of five categories to construct the indicator system of comprehensive landscape quality assessment of urban forest parks. In view of requirements of landscape quality assessment of urban forest parks, a niche suitability model (NSM) was introduced. On the basis of analysis and improvement, the spatial niche suitability model (SNSM) was constructed by using a weighted average method. Then, the application test of SNSM was carried out taking Nanjing Zijinshan National Forest Park as the research target. The assessment results show that the landscape quality of Nanjing Zijinshan National Forest Park showed a slow upward trend from 2010 to 2018, and was at the lower middle level in 5A scenic area; at the same time, due to buildings increasing and environmental pollution, forest landscape quality showed a slow downward trend. The assessment results of spatial niche suitability model are in line with the actual situation of landscape quality of Nanjing Zijinshan National Forest Park, and provide an effective quantitative analysis method for urban forest parks to strengthen landscape quality management and prevent landscape quality risks.